Carcass Traits, Mineral Retention, Blood Biochemistry and Economics of Broiler Chicken Fed Inorganic, Organic and Nano Zinc Supplemented Diets - Shubhnish; V.S. Panwar; B.S. Tewatia; Jyotsana (Indian Journal of Animal Nutrition, 2024)
The present study was planned to assess the effect of inorganic, organic and nano zinc supplemented diets on different carcass traits, haematological and serological parameters of broiler birds. One hundred and sixty one dayold broiler chicks were equally and randomly distributed into four treatment (T1, T2, T3 and T4) groups which were subdivided into four replicates having ten birds in each. Birds were reared on deep litter system up to 6 weeks of age. T1 group was kept as control and offered maize-soybean meal based diet without any source of zinc in mineral mixture. Treatment groups T2, T3 and T4 were supplemented with inorganic, organic and nano zinc, respectively.The carcass characteristics data revealed that dressed weight and the weight of liver, gizzard and kidney significantly increased(P<0.05)in nano zinc supplemented group (T4) in comparison to T1, T2, and T3 groups. Also the abdominal fat % was recorded lowest in T4 group among all treatment groups. Breast and thigh meat composition showed thatnano zinc supplemented group (T4)had highest(P<0.05)crude proteinand lowest moisture & ether extract percentage among all other treatment groups. Zinc retention in the body was significantly higher (P<0.05) in T4 group followed by T3, T2 and T1 group. In haematological parameters of broiler birds a significant increase(P<0.05) in HB, RBC and WBC was seen in nano zinc supplemented group in comparison to all other groups. Similarly in serological parameters the T4 group showed the highest reduction(P<0.05) in cholesterol, triglyceride and LDL while highest levels of HDL in comparison to other groups. The present study thus revealed that zinc in nanoform had a significantimprovement in carcass traits and different blood parameters in comparison to thetreatment groups supplemented zinc in organic and inorganic form.